Trans-jugular intrahepatic porto-systemic shunt placement for refractory ascites: a 'real-world' UK health economic evaluation. Issue 3 (22nd March 2013) - Parker, Matthew J; Guha, Neil; Stedman, Brian; Hacking, Nigel; Wright, Mark
Abstract : Objective: To assess the benefit of trans-jugular intrahepatic porto-systemic shunt (TIPS) placement for refractory ascites. Design: A retrospective observational study of all patients undergoing TIPS for refractory ascites in our hospital between 2003 and 2012. Setting: Secondary care. Patients: Cirrhotic patients with refractory ascites. Main outcome measures: We examined direct real-world (National Health Service) health related costs in the year before and after the TIPS procedure took place. Data were collected relating to the need for reintervention and hepatic encephalopathy. Results: Data were available for 24 patients who underwent TIPS for refractory ascites (86% of eligible patients). TIPS was technically successful in all cases. Mean number of bed days in the year prior to TIPS was 30.3 and 14.3 in the year following (p=0.005). No patient had ascites at the end of the year after the TIPS with less requirement for paracentesis over the course of the year (p<0.001). Mean reduction in cost was £2759 per patient. TIPS was especially cost-effective in patients requiring between 6 and 12 drains per year with a mean saving of £9204 per patient. Conclusions: TIPS is both a clinically effective and economically advantageous therapeutic option for selected patients with refractory ascites.